Pemantapan Literasi Digital oleh Pendidik dan Peserta Didik dalam Menghadapi Era Society 5.0 - Agung, Fatikh Catur Wahyudi (Revorma: Jurnal Pendidikan dan Pemikiran, 2024)
Society Era 5.0 is a concept that helps us understand how human civilization has evolved over time. By understanding historical developments in the Society Era, we can have better insight into the changes that occur in society and how we can adapt and develop in an ever-changing era. Digital literacy is very important in everyday life, especially in the current era of society 5.0. We can improve our digital literacy by verifying information sources, maintaining privacy, creating strong password protection, maintaining digital ethics, updating digital knowledge, and sharing validated knowledge. There are nine elements of digital literacy: Social Networking, Transliteracy, Maintaining Privacy, Managing Digital Identity, Creating Content, Organizing and Sharing Content, Reusing/Repurposing Content, Filtering and Selecting Content and Self Broadcasting. Meanwhile, the strategies that must be implemented are: critical thinking, utilizing information technology and understanding digital culture. In the world of education, we must be able to understand the four stages of problem solving, namely: understanding the problem, making a solution plan, carrying out calculations and checking the results again. Keywords: Educators, Digital Literacy, Era Society 5.0.